Rubinstein Taybi Syndrome - Das, N; Ghosh, N; Biswas, S; Nayek, K (Journal of Nepal Paediatric Society, 2013)
Rubinstein Taybi is a rare genetic syndrome with characteristic facial features, broad thumb and toes, mental retardation. Diagnosis is mainly clinical. Here we report a 2 and ½ year old female child with typical facial features and other anomalies characteristics of Rubistein Taybi syndrome. Among the different features described-polydactyly, syndactyly, micrognathia are occasional abnormalities to be found in this syndrome. Bilateral pits on posterior aspect of helix is also a feature described in very few literatures. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7091 J Nepal Paediatr Soc. 2013;33(1):68-69